Congestion offsets: Transforming cities by letting buses compete - Bradley, Matthew; Kenworthy, Jeffery (Eco-Logica Ltd, 2012)
Cities around the world have been unable to keep up with demand for road space, and as a result suffer from congestion. This paper argues that the consequence of this congestion has been not just poorly performing roads, but a structurally inefficient urban transport solution, due to the impact of congestion on bus services. As a way of controlling congestion, road pricing has been rejected by most cities because it is difficult to sell to the public and difficult to deploy. An examination of both the strengths and weaknesses of road pricing is used as a basis from which to develop an alternative method of congestion control, namely congestion offsets. This approach treats roads as a commons, and does not argue for the creation of a market for road space, as road pricing does. It is argued that congestion offsets would allow congestion to be controlled in a simple and fair manner, thereby enabling buses to emerge as a real competitor to cars in urban areas. The historical absence of congestion control in cities has allowed massive distortions to build up; cities have become awash with both cars and bitumen. Congestion offsets would allow these distortions to be slowly unwound, thus helping to transform cities more into how, it is argued, they should have always been.